2018
DOI: 10.1186/s41935-018-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot- cross sectional study of palatal Rugae shape and direction among Egyptians and Malaysians

Abstract: Background: To evaluate the role of different morphological palatal rugae patterns (palatal print) as a tool for personal identification. Method: A pilot cross-sectional study was carried out on 60 Egyptian subjects and 60 Malaysian subjects. All were above 6 years old, nonsmokers and were sharing the same dietary habits. Palatal impressions were taken from the subjects and a rugogram was issued. Many parameters were included in the rugogram. Rugae shape, direction and unification pattern were the main paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(40 reference statements)
4
5
0
1
Order By: Relevance
“…This finding broadly supports the results of earlier reports. 4,6,7,[9][10][11][13][14][15]18,22 The current study found that only the number of circular rugae was significantly higher in females than males, similar to an earlier report. 7 However, the findings of our study do not support the results of previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding broadly supports the results of earlier reports. 4,6,7,[9][10][11][13][14][15]18,22 The current study found that only the number of circular rugae was significantly higher in females than males, similar to an earlier report. 7 However, the findings of our study do not support the results of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…A considerable amount of literature exists on diverse topics like genetic predisposition, 2 the prevalence of various morphological patterns, [4][5][6][7][8][9] and differences in PR's morphology concerning sex. 2,[10][11][12][13][14][15][16][17] To date, there has been little agreement on whether sex can be predicted with the help of PR patterns 11,18 and most of the studies recommended the use of PR along with other methods for the identification of sex. With this background, we aimed to use the morphological analysis of palatal rugae patterns to assess sex in a South Indian adult population.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this study group had more divergent type of rugae than convergent rugae. This finding was similar to the unification pattern observed in Egyptians and Indians but in contrast with Sudanese, Libyans, Serbians, and Bengalis which were predominantly convergent (23,27–29,32,34). The unification pattern was not statistically different between the sibling groups in this study.…”
Section: Discussionsupporting
confidence: 83%
“…This study group showed more backward directed rugae compared to forward and perpendicular rugae which is similar to the Bengali population (28). In contrast, forward directed rugae was predominant in Sudanese, Egyptians, Turkish, Gujarati, and Indians (22,27,(29)(30)(31)(32)(33). Generally, the population worldwide would show more forward directed rugae because there is a decrease in backward directed rugae with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation